Georgia Architectural and Historic Properties Survey of Labelle Ave. [4], Sycamore, Turner County, Ga., 1981 - Barton and Harbin (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Labelle Ave. [4], Sycamore, Turner County, Ga., 1981. Saddlebag house plan with tin gabled roof. Shed porch. Asbestos shingle siding. Double sash windows with 6/6 lights. Interior chimney removed. Brick piers. Poor condition. Date of Construction: c. 1905. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Labelle Ave. [4], Sycamore, Turner County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scans. 0 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 26.4 MB (27,743,700 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Sycamore (Ga.); Turner County (Ga.)